Gandhi: The Years that Changed 1914-1948 - Ramachandra Guha (Allen Lane/ Penguin Random House India, 2018)
Gandhi lived one of the great 20th-century lives. He inspired and enraged, challenged and delighted millions of men and women around the world. He lived almost entirely in the shadow of the British Raj, which for much of his life seemed a permanent fact, but which he did more than anyone else to bring down. In a world defined by violence and warfare and by fascist and communist dictatorships, he was armed with nothing more than his arguments and example. While fighting for national freedom, he also attacked caste and gender hierarchies, and fought (and died) for inter-religious harmony. This magnificent book tells the story of Gandhi's life from his departure from South Africa to his dramatic assassination in 1948. It has a Tolstoyan sweep, showing us Gandhi as he was understood by his contemporaries, with new readings of his arguments with (among others) Ambedkar, Jinnah, and Churchill, and new insights on our freedom movement and its many strands. Drawing on never-before-seen sources and animated by its author's wonderful sense of drama and politics, Gandhi: The Years That Changed the World is the most ambitious book on the father of the nation.